Current status and management strategies of medical waste in Jinshan District， Shanghai - WANG Jinzhen; JIANG Yan; JIANG Yong; YANG Haojie; YANG Guang; FAN Lei; NIE Lianlian; YANG Danhong (Shanghai yufang yixue, 2025)
ObjectiveTo assess the current status of medical waste management in Jinshan District of Shanghai, China, to identify existing issues, and to provide a scientific basis for formulating targeted strategies.MethodsData were collected from the routine supervision and inspection records of the Jinshan District Health Commission Supervision Institute from 2017 to 2021, covering all aspects of medical waste management, including collection, classification, transportation, storage, and administrative penalties.ResultsThe compliance rates for the establishment of institutional frameworks, staffing, internal handover, and registration in medical and healthcare institutions all exceeded 95.00%. However, only 2.31% of the medical and healthcare institutions met the 48-hour storage limit requirement for medical waste. Private institutions had significantly lower compliance rates (P<0.05) in aspects such as proper classification and collection, maintaining records for three years, adhering to the 48-hour storage limit, refraining from commercial transactions, timely disinfection and cleaning, and implementing emergency measures for waste loss. Compliance rates also varied among different types of institutions regarding the establishment of temporary storage facilities and the implementation of the transfer manifest system, with community healthcare institutions exhibiting relatively lower compliance rates (P<0.05). Over the past five years, private medical and healthcare institutions accounted for 63.33% of administrative penalty cases.ConclusionWhile medical waste management in Jinshan District, Shanghai, has gradually become more standardized, challenges remain. To address the issue of medical waste being stored for over 48 hours, medical waste transfer stations should be established to improve transfer efficiency and ensure complete waste collection. Additionally, for private and community healthcare institutions, weak links in management should be addressed by establishing medical waste quality control teams, enhancing supervision through digital tools, and optimizing management processes to comprehensively elevate medical waste management.